LINE SHAPES OF DOPPLER-FREE RESONANCE IN SRFM: STRONG ATOM-WALL INTERACTION AND PRESSURE EFFECT ON THE FREQUENCY SHIFT OF AN ALKALI VAPOR (Sciences & Technology. A, exactes sciences, 2003)
The attractive potential energy between the atoms of rubidium vapor and a dielectric wall has been investigated by monitoring the reflection light at the interface. The atom- wall interaction potential of the form V(z) = - C /z3 (z: atom-wall) allows to predict experimental results only for weak regime, i.e., where C